Mechanisms of cultural diversity in urban populations - Harin Lee; Nori Jacoby; Romain Hennequin; Manuel Moussallam (Nature Communications)
Abstract Large cities exhibit greater cultural diversity. Due to limited data on individual behaviour, previous research could not discern whether this stems from demographic heterogeneity or enhanced individual cultural exploration. Analysing 250 million listening events from 2.5 million users across France, Brazil, and Germany, we investigate mechanisms driving urban cultural diversity. We assess the collective shared musical repertoire in each geographical area, while concurrently measuring individuals’ music engagement breadth through listening histories. Cross-culturally, both collective diversity and individual breadth increase with population size, aligning with cultural evolution and urban scaling theories. While demographic factors such as age, gender, income, immigration, education, and social connections influence these trends, especially in highly populated areas, they do not fully explain the observed patterns. This suggests large cities are culturally diverse not only because they aggregate people from varied backgrounds but also due to greater opportunities created for cultural interactions and discovery.